Teacher Strategies in Increasing Students' Learning Interest on Multimedia based Islamic Learning at Madrasah Aliyah Luwu - Nurdin Kaso; Dodi Ilham (Jurnal Studi Guru dan Pembelajaran, 2020)
This study aims to describe multimedia technology-based learning in increasing interest in PAI learning. This study clarifies a phenomenon and the reality by explaining the variables related to the problem under study. Researchers identified problems related to developing multimedia technology-based PAI learning media at Madrasah Aliyah in Luwu Regency. This research is qualitative. This research was conducted in six Madrasah Aliyah in Luwu Regency, consisting of Madrasah Aliyah Negeri Luwu, Madrasah Aliyah Salubanga, Madrasah Aliyah Sampano, Madrasah Aliyah Wathaniyah Belopa, Madrasah Aliyah Pondok Pesantren Almubarak DDI Tobarakka, Madrasah Aliyah Al-Mawatsir Padang Kalua. Sources of data in this study are classified into two types, namely primary and secondary data sources. The data collection techniques that will be used in this study are observation, interviews, and documentation. This study's data processing and analysis technique uses an interactive model proposed by Miles and Huberman. The use of multimedia technology-based learning media in PAI subjects at Madrasah Aliyah in Luwu Regency is relatively small compared to many Islamic Educators. The number of PAI teachers at Madrasah Aliyah in Luwu Regency is 17 PAI teachers, but only 3 (17.64%) use multimedia technology in the learning process of Islamic Religious Education. Increasing students' interest in learning in PAI subjects at Madrasah Aliyah in Luwu Regency for teachers who use multimedia technology-based learning media is very good. It is because the use of multimedia technology in the learning process has a significant impact on students.